Leviticus and Numbers - Brenner, Athalya; Lee, Archie Chi Chung (Minneapolis : Fortress Press, 2013)
"The Texts @ Contexts series gathers scholarly voices from diverse contexts and social locations to bring new or unfamiliar facets of biblical texts to light. Leviticus and Numbers focuses attention on practices and ideals of behavior in community, from mourning and diet to marriages licit and transgressive, examining all of these from a variety of global perspectives and postcolonial and feminist methods. How do we deal with the apparent cultural distances between ourselves and these ancient writings; what can we learn from their visions of human dwelling on the earth?"--Book description, Amazon.com.
Issues in Leviticus. Landed interpretation / Kristel A. Clayville -- USDA or YHWH? / Joseph Ryan Kelly -- "Do not bare your heads and do not rend your clothes" (Leviticus 10:6) / Yael Shemesh -- Slave wives and transgressive unions in Biblical and ancient Near Eastern laws and literature / Helen R. Jacobus -- The notion of k-p-r in the book of Leviticus and Chinese popular religion / Sonia K. Wong -- Golden do's and don'ts / Carole R. Fontaine -- Issues in Numbers. Bitter waters (Numbers 5), flood waters (Genesis 6-9), and some theologies of exile and land / Diana Lipton -- From the well in Midian to the Ba'al of Peor / Yonina Dor -- Numbers 25 and beyond / Anthony Rees -- Indicting YHWH / N asili Vaka'uta -- A queer womanist Midrashic reading of Numbers 25:1-18 / Wil Gafney -- Assessing female inheritance of land in Nigeria with the daughters of Zelophehad narrative (Numbers 27:1-11) / AMadi Ahiamadu -- Reading iconoclastic stipulations in Numbers 33:50-56 from the pluralistic religious context of China / Archie C.C. Lee.
Includes bibliographical references (pages 227-251)-and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible; Bible; Criticism, interpretation, etc..